Low-energy electron beam has severe impact on seedling development compared to cold atmospheric pressure plasma - A. Waskow (Nature Portfolio, 2021)
Abstract Sprouts are germinated seeds that are often consumed due to their high nutritional content and health benefits. However, the conditions for germination strongly support the proliferation of present bacteria, including foodborne pathogens. Since sprouts are consumed raw or minimally processed, they are frequently linked to cases of food poisoning. Therefore, a seed decontamination method that provides efficient inactivation of microbial pathogens, while maintaining the germination capacity and quality of the seeds is in high demand. This study aimed to investigate and compare seed decontamination by cold atmospheric-pressure plasma and low-energy electron beam with respect to their impact on seed and seedling quality. The results show that both technologies provide great potential for inactivation of microorganisms on seeds, while cold plasma yielded a higher efficiency with 5 log units compared to a maximum of 3 log units after electron beam treatment. Both techniques accelerated seed germination, defined by the percentage of hypocotyl and leaf emergence at 3 days, with short plasma treatment (< 120 s) and all applied doses of electron beam treatment (8–60 kGy). However, even the lowest dose of electron beam treatment at 8 kGy in this study caused root abnormalities in seedlings, suggesting a detrimental effect on the seed tissue. Seeds treated with cold plasma had an eroded seed coat and increased seed wettability compared to electron beam treated seeds. However, these effects cannot explain the increase in the germination capacity of seeds as this was observed for both techniques. Future studies should focus on the investigation of the mechanisms causing accelerated seed germination and root abnormalities by characterizing the molecular and physiological impact of cold plasma and electron beam on seed tissue.